Correlation analysis between multiple mini-interviews during medical student selection and their academic performance - Adam, Siti Khadijah; Hod, Rafidah; Mahayidin, Hasni; Ahmad, Zalinah; Salihan, Safuraa (Penerbit Universiti Sains Malaysia, 2024)
Multiple mini-interviews (MMI) have been used as a tool in the selection of medical students to evaluate their interpersonal and intrapersonal attributes. It is suggested that rigorous evaluation in MMI may predict academic performance during medical training. Thus, this study aims to determine the relationship between MMI scores and subsequent academic performance at the end of the preclinical phase. MMI scores for the academic session 2019/2020 intake in Universiti Putra Malaysia were gathered. The dependent variables were the students’ academic performance at the end of the preclinical phase involving the Professional Examination and Professionalism and Personal Development (PPD) course. No significant positive correlation was observed between MMI and total Professional Examination scores. Total MMI and empathy station scores have a weak positive relationship with objective structured clinical examination (OSCE) marks. There was also a significant positive correlation between resilience station scores and PPD peer assessment marks. In contrast, there was a negative correlation between Malay language station scores and the theory component of Professional Examination marks. This study suggests that MMI has the potential to predict in-programme clinical performance and professionalism characteristics. Studies with larger cohorts are essential to support this evidence.